Alex, you're glowing - Gallagher, Diana G. (New York : Pocket Books, 1995)
Alex encounters many problems on her first day of junior high school.
"A Minstrel book.".
"A Minstrel paperback original"--T.p. verso.
"Adapted from a teleplay by Ken Lipman and Thomas W. Lynch.".
Keywords: Psychokinesis -- Fiction; Schools -- Fiction